Influences of Sedimentary Environments and Volcanic Sources on Diagenetic Alteration of Volcanic Tuffs in South China - Nina Gong (Nature Portfolio, 2018)
Abstract Permian-Triassic (P-Tr) altered volcanic ashes (tuffs) are widely distributed within the P-Tr boundary successions in South China. Volcanic altered ashes from terrestrial section-Chahe (CH) and marine section-Shangsi (SS) are selected to further understand the influence of sedimentary environments and volcanic sources on diagenetic alterarion on volcanic tuffs. The zircon 206Pb/238U ages of the corresponding beds between two sections are almost synchronous. Sedimentary environment of the altered tuffs was characterized by a low pH and did not experience a hydrothermal process. The dominant clay minerals of all the tuff beds are illite-smectite (I-S) minerals, with minor chlorite and kaolinite. I-S minerals of CH (R3) are more ordered than SS (R1), suggesting that CH also shows a higher diagenetic grade and more intensive chemical weathering. Besides, the nature of the volcanism of the tuff beds studied is derived from different magma sources. The clay mineral compositions of tuffs have little relation with the types of source volcanism and the depositional environments. Instead, the degree of the mixed-layer clay minerals and the REE distribution are mainly dependent upon the sedimentary environments. Thus, the mixed-layer clay minerals ratio and their geochemical index can be used as the paleoenvironmental indicator.